(untitled) (Stylos, 2019)
In Metamorphoses XIV 260-270, the account of the arrival at Circe’s island differs from its sources in the form of refering to the activity of weaving/tissue and singing. Her assitants, the Nymphs, go out to greet the newcomers and make them enter; it’s mentioned that they attend Circe at all times in preparation of the magic spells. It’s explicitly refused that they work in tissue, and is described in detail their task of classifying herbs and their supervision by Circe (264-270). The present work intends to analyze this fragment of Metamorphoses, in order to understand the denial of this character trait as a way of transposition, in metaphorical terms, to the particular narrative plot of this “Ovidian Aeneid”, being Circe in the center.